Diagnostic Accuracy of Complicated Pleural Effusion Score to differentiation between Tuberculous Pleural Effusion and Complicated Parapneumonic Effusions (Journal of Fatima Jinnah Medical University, 2024)
Background: In tuberculosis-endemic areas, the complicated pleural effusion score aids in distinguishing between CTPE and CPPE, which present with similar symptoms. The aim of this study was to assess the diagnostic accuracy of the complicated pleural effusion score to distinguish between CTPE from CPPEPatients and methods: This was a cross-sectional study conducted at the Institute of Tuberculosis and Chest Medicine (outdoor and indoor locations), Mayo Hospital Lahore. The study included 70 patients aged 18–80 years with patients with clinical suspicion of complicated Parapneumonic pleural effusion and Tuberculous Pleural effusion were included in current study complicated parapneumonic or tuberculous pleural effusion. Exclusions were empyema, suspected/confirmed pleural malignancy, bleeding diathesis, and pregnancy. After taking informed written consent, I/V line was passed and diagnostic pleural tap was done under Ultrasound guidance with 50cc Disposable syringe under aseptic measures and pleural fluid was sent for complete analysis including PH, Glucose, Total leukocyte count with differential cell count and ADA levels estimation. After that, COMPLES score was calculated. Patients with a COMPLE score 12 were presumptively diagnosed with parapneumonic pleural effusion.Results: Mean COMPLES score was 12.05±4.91. As per cut point of COMPLES score 36 (51.4%) patients had been diagnosed with tuberculous pleural effusion and 34 (48.6%) had been diagnosed with parapneumonic pleural effusion. Sensitivity and specificity of COMPLES score was 100% and 81.82%. While the respective values for positive and negative prediction accuracy were 76.74% and 100%.Conclusion: The COMPLES score proved highly effective in differentiating tuberculous pleural effusion from complicated parapneumonic effusions. A score >12 identified tuberculous pleural effusion with 100% sensitivity and 81.82% specificity. The positive predictive value was 76.74%, the negative predictive value was 100%, and the overall diagnostic accuracy was 88.57%.
Keywords: Diagnostic; Precise; Difficult; Pleural effusion; Complicated Parapneumonic effusions